1985
DOI: 10.5636/jgg.37.541
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anomalies in the western part of the North Anatolian Fault Zone and their implications for active fault structure.

Abstract: In 1981 and 1982 intensive observations of the geomagnetic field were carried out in a possible seismic gap region in the western part of the North Anatolian Fault Zone to trace on active fault and also to accumulate geomagnetic data for earthquake prediction research. The data of magnetic anomalies obtained from profile measurements across the fault were interpreted to reveal an anomalous magnetic structure associated with the active fault. In order to confirm our results thus derived in the Iznik-Mekece area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…The ground magnetic survey along the North Anatolian fault defined a number of coherent magnetic anomalies supposed to be caused by sheet-shaped sources (ISIKARA et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The ground magnetic survey along the North Anatolian fault defined a number of coherent magnetic anomalies supposed to be caused by sheet-shaped sources (ISIKARA et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic anomalies found near the active fault constituting the southern branch could be well interpreted in terms of a dike-like structure, which in turn provided information on the surface extension of the fault plane as well as its dip angle I IKARA et al, 1985). Folding may also disturb the subsurface magnetic structure and yield a magnetic anomaly to be observed at the Earth's surface.…”
Section: Introductionmentioning
confidence: 88%
“…We can apply a dike model, as used by ISIKARA et al (1985), to the magnetic anomaly observed along the line A. Figure 10 shows the result of inversion for a dike model.…”
Section: Interpretation Of the Observed Anomaliesmentioning
confidence: 99%